QoS Management for Broadband IEEE 802.16 based Networks in FDD Mode - Rangel, V.; Macedo, Y.; Ortiz, L.; Gómez, J.; Aquino, R.; Edwards, A. (Elektronika ir Elektrotechnika, 2010)
The design and performance analysis of a scheduling technique for the provision of QoS over Broadband Wireless Access Networks (BWA) is presented. The proposed scheduling algorithm is based on the MAC protocol of the IEEE 802.16 standard and focuses on the uplink channel, which is the limiting factor of BWA networks and is critical in the delivery of services to individual users. Although the IEEE 802.16 standard had proposed several QoS service classes for various types of applications, they do not suggest how to schedule traffic to fulfill timing critical services such as compressed/uncompressed voice, audio and video streams. We have derived a mechanism called EBSA that combines several scheduling algorithms to closely match VBR-like and CBR-like traffic over the IEEE 802.16 air interface. Simulation results show that EBSA provides real-time services with very low access delays even during congestion periods. Ill. 7, bibl. 14 (in English; summaries in English, Russian and Lithuanian).